Hyponatremia as a Predictor of Cryptococcal Meningitis and Death Among Asymptomatic Persons With HIV and Cryptococcal Antigenemia. (28th March 2023) - Lehman, Alice; Nalintya, Elizabeth; Wele, Abduljewad; Kirumira, Paul; Naluyima, Rose; Namuli, Teopista; Turya Musa, Fred; Skipper, Caleb P; Meya, David B; Boulware, David R; Rajasingham, Radha
Abstract: Among persons with human immunodeficiency virus–associated cryptococcal meningitis serum hyponatremia is a risk factor for mortality; however, the role of hyponatremia in persons with asymptomatic cryptococcal antigenemia is unknown. We found that serum hyponatremia ≤130 mmol/L is an independent risk factor for progression to meningitis and death in asymptomatic persons with cryptococcal antigenemia.